Perceptual factors contribute more than acoustical factors to sound localization abilities with virtual sources - Andéol, Guillaume; Savel, Sophie; Guillaume, Anne (Frontiers in Neuroscience, 2015)
Human sound localization abilities rely on binaural and spectral cues. Spectral cues arise from interactions between the sound wave and the listener’s body (head related transfer function, HRTF). Large individual differences were reported in localization abilities, even in young normal-hearing adults. Several studies have attempted to determine whether localization abilities depend mostly on acoustic cues or on perceptual processes involved in the analysis of these cues. These studies have yielded inconsistent findings, which could result from methodological issues. Here, we measured sound localization performance with normal and modified acoustic cues (i.e., with individual and non-individual HRTFs, respectively) in 20 naïve listeners. Test conditions were chosen to address most methodological issues from past studies. Procedural training was provided prior to sound localization tests. The results showed no direct relationship between behavioral results and an acoustical metric (spectral-shape prominence of individual HRTFs). Despite uncertainties due to technical issues with the normalization of the HRTFs, large acoustic differences between individual and non-individual HRTFs seemed to be needed to produce behavioral effects. A subset of 15 listeners then trained in the sound localization task with individual HRTFs. Training included either visual correct-answer feedback (for the test group) or no feedback (for the control group), and was assumed to elicit perceptual learning for the test group only. Few listeners from the control group, but most listeners from the test group, showed significant training-induced learning. For the test group, learning was related to pre-training performance (the poorer the pre-training performance, the greater the learning amount) and was retained after one month.The results are interpreted as being in favor of a larger contribution of perceptual factors than of acoustic factors to sound localization abilities with virtual sources.